Subtitle translation of American sitcom The Big Bang Theory from the perspective of eco-translatology - Cao, Jing; Mansor, Nor Shahila; Ang, Lay Hoon; Abu Ujum, Diana (Academy Publisher, 2022)
Eco-translatology is a theory of translation put forward by Professor Hu Genshen, which regards translation as a process of “selective adaptation” and “adaptive selection”. The popularity of American TV dramas has aroused a huge demand for subtitle translation, resulting in the rapid growth of subtitle translation by fansub groups and increasing enthusiasm for subtitle translation studies in China. While there is no accordant idea about the understanding of subtitle translation of TV dramas on the internet translated by fansub groups. Based on the theoretical framework of Eco-translatology theory, this study examines the subtitle translation of The Big Bang Theory to analyze translators’ “selection” and “adaptation” on linguistic, cultural, and communicative dimensions. It also pays attention to the inappropriate selection of translation techniques made by the fansub groups. The analysis shows that in the translation process of The Big Bang Theory’s subtitles, the translators adopted various translation techniques which include the applications of buzzwords, Chinese idioms, annotations, and free translation to implement adaptive selection in linguistic, cultural, and communicative dimensions. And the fansub groups make some inappropriate selections as abusing the Chinese dialect in translation. These findings attempt to provide a reference for subtitle translation of American TV dramas available on the internet, as well as evidence of the explanatory power of Eco-translatology theory in subtitle translation studies, in order to supplement a new perspective on subtitle translation and more attention on this developing translation theory.